Sources of variation in self-incompatibility in the Australian forest tree, Eucalyptus globulus - McGowen, Marian H. (Oxford University Press, 2010)
BACKGROUND AND AIMS: One of the major factors affecting the outcrossing rate in Eucalyptus globulus is thought to be the inherent self-incompatibility (SI) level of the female tree. SI in this species is mainly due to late-acting pre- and post-zygotic mechanisms operating in the ovary, and not S alleles. This study aimed to assess the phenotypic variation in SI levels within E. globulus and determine its genetic control and stability across pollination techniques, sites and seasons. METHODS: SI levels were estimated for 105 genotypes originating from across the geographical range of E. globulus over multiple years of crossing. Separate grafted trees of some genotypes growing at the same and different sites allowed the genetic basis of the variation in SI to be tested and its stability across sites and seasons to be determined. The SI level of a tree was measured as the relative reduction in seeds obtained per flower pollinated following selfing compared with outcross pollinations. Thus, if seed set is the same, SI is 0 %, and if no self seed is set, SI is 100 %. KEY RESULTS: The average SI in E. globulus was 91 % and genotypes ranged from 8 to 100 % SI. Most genotypes (>75 %) had SI levels >90 %. There were highly significant differences between genotypes and the within-site broad-sense heritability of percentage SI was high (H(2) = 0·80 ± 0·13). However, there was evidence that growing site, and to a lesser extent season, can affect the expression of SI levels. Trees with low reproductive loads produced relatively more seed from selfed flowers. CONCLUSIONS: There is a strong genetic basis to the phenotypic variation in SI in E. globulus within a site. However, the level of SI was affected, but to a lesser extent, by the environment, which in part may reflect the higher probability of selfed zygotes surviving on sites or in seasons where competition for resources is less.